2022
DOI: 10.1364/ol.457462
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient detection of near-infrared optical vortex modes with frequency upconversion

Abstract: Vortex beams carrying orbital angular momentum (OAM) have been widely applied in optical manipulations, optical micromachining, and high-capacity optical communications. Vortex mode detection is very important in various applications. However, the detection of near-infrared vortex modes is still difficult because of the wavelength limitations of the detection device. Here, we present a study on measuring optical near-infrared vortex modes with frequency upconversion, which can convert a near-infrared beam into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Our results verify that the Rayleigh range of the SH beam is the same as that of the fundamental beam during the SHG process. The lobes of the SH beam obtained via the tilted lens method allow us to determine the TC carried by the fundamental infrared vortex beams [46]. In addition, we demonstrated that SHG is an effective method for obtaining vortex beams with high mode purity.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Our results verify that the Rayleigh range of the SH beam is the same as that of the fundamental beam during the SHG process. The lobes of the SH beam obtained via the tilted lens method allow us to determine the TC carried by the fundamental infrared vortex beams [46]. In addition, we demonstrated that SHG is an effective method for obtaining vortex beams with high mode purity.…”
Section: Introductionmentioning
confidence: 84%
“…The power of the generated SH vortex beam and the transmi ed fundamental vortex beams is directly measured using two power meters (Thorlabs PM 100D). Both the off-axis interference method [49] and tilted lens method [46,50] are used to measure the TCs carried by the fundamental/SH vortex beams. For the former method, the TEM 00 Gaussian beam is used as the reference to interfere with the generated vortex beam with a small included angle.…”
Section: Methodsmentioning
confidence: 99%
“…al detected the vortex beam up to 100-order by employing this phase [22]. Furthermore, Yujia Wu and Yongqiang Yang extended this method to detect the OAM of the near-infrared optical vortex [23] and terahertz optical vortex [24], respectively. However, the conversion of the beams array is not analyzed in these reports.…”
Section: Introductionmentioning
confidence: 99%